Participatory action research as driver of democratic citizenship and social change - Delgado Algarra, E. (2015)
This article presents a review of the basics of participatory action research in order to specify the links between the research itself, democratic citizenship and social change. In the first section, it is performed an exploration of some research and experiences about participatory action research in the United Kingdom, the United States, Japan and China. The changes associated with the conclusions of these experiences provides the recognition of its paradigmatic basis (sociocritic paradigm). On the one hand, after contextualizing the process of participatory action research, a description of its features and stages is performed; specifying the necessary teaching profile. On the other hand, a review of models of citizenship and the democratic principles underlying the above mentioned research model is carried out. Regarding all these aspects, the necessary arguments are set to define civic basis on which participatory action research is founded. In conclusion, this research model is based on reflection onto action and change, mainly linking two models of citizenship: the radical and justice oriented, under the principles of participative democracy.